An investigation of partial meaning and non-equivalence in English translations of Ekegusii kinship terms (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The main challenge that translators face is that of non-equivalence as the source language (SL) and the target language (TL) almost always have cultural and linguistic differences (organize words differently). Accordingly, one needs to be aware of the linguistic differences between the two cultures. A group uses a set of terms to name the people they are related to by blood, marriage or adoption which should be recognized by members of the speech community. This study explores kinship terms in Ekegusii, a language that has been coded as E42 in Guthrie's (1971) classification of Bantu languages and belongs to the interlacustrine zones, namely D and E. Both Ekegusii and English languages have their unique kinship term systems which pose translation problems with regard to equivalence. Unlike English nouns that denote family relations in a pretty straightforward way, Ekegusii™s way of addressing family members and relatives differs and to some degree it may be difficult to those who are not familiar with the Ekegusii culture. Consequently, this paper investigates the problem of non-equivalence at word level in translation between Ekegusii and English. The paper presents background knowledge and different approaches related to non-equivalence. Subsequently, conceptual kinship terminologies are contrasted to prove that there is a significant linguistic gap between Ekegusii and English. The paper then proposes a classification of non-equivalence at word level based on Mona Bakers point of view. Finally, the paper suggests effective strategies to deal with non-equivalence at word level in translation of Ekegusii kinship terms.